Effect of Price and Service Quality on Customer Satisfaction and Its Implications on Customer Loyalty PT. XYZ - Rahmat Haryanto; Arifin Sitio (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This study aims to analyze the Effect of Price and Service Quality on Customer Satisfaction and Its Implications on the Customer Loyalty of PT. XYZ This type of research used in this study is Causal Research Type. The population in this study were all patients who had visited and had received health services at PT. XYZ in 2018 as many as 43,476 people. Determination of the number of samples using the formula Slovin so as to get 100 respondents. The analysis method used is the regression analysis test through SPSS version 25. The results of this study indicate that (1) Price has a positive and significant effect on patient satisfaction, (2) Service Quality has a positive and significant effect on Patient Satisfaction, (3) Price influences positive and significant impact on Patient Loyalty, (4) Service Quality has positive and significant impact on Patient Loyalty, (5) Patient Satisfaction has positive and significant impact on Patient Loyalty, and (6) There is a positive indirect effect between Price and Quality of Service on loyalty through patient satisfaction, meaning through patient satisfaction can increase patient loyalty.